CONNECTING STATISTICS, PROBABILITY, ALGEBRA AND DISCRETE MATHEMATICS - Lopez-Blazquez, F; Nunez-Valdes, J; Recacha, S; Villar-Linan, M.T (TWMS journal of applied and engineering mathematics, 2024)
In this paper, we connect four different branches of Mathematics: Statistics, Probability, Algebra and Discrete Mathematics with the objective of introducing new results on Markov chains and evolution algebras obtained by following a relatively new line of research, already dealt with by several authors. It consists of the use of certain directed graphs to facilitate the study of Markov chains and evolution algebras, as well as to use each of the three objects to make easier the study of the other two. The results obtained can be useful, in turn, to link different scientific disciplines, such as Physics, Engineering and Mathematics, in which evolution algebras are considered very interesting tools. Keywords: Evolution algebras; directed graphs; Markov chains; mathematical modellings. AMS Subject Classification: 17D99; 05C20; 60J10; 60J25.